Determination of Reliability of Different Reference Lines for Photogrammetric Assessment - Müge Aksu; Demet Kaya; İlken Kocadereli (Galenos Yayinevi, 2008)
The aim of this study is to determine the most reliable reference line among five different reference lines used for photogrammetric measurments obtained from women's standardized extraoral photographs. 35 healty females with a mean age of 23.25±2.64 years were examined in this study. Soft tissue measurements were done directly from the lateral and frontal view on each face. Extraoral photographs were taken with a standardized method from a constant distance and at the same lighting condition. The photographs were transfered to the computer and parameters were measured on each photograph by using three reference lines on the lateral view (Ex-Ex, En-En, P-P) and two reference lines on the frontal view (Sa-Sba, TEx). Magnification error was corrected by using values of reference lines. Three different values frontally and two different values laterally were obtained for each parameter according to the reference lines. These values were tested with repeated measure ANOVA and compared with the direct values obtained from the patients. For the lateral measurements, the values according to Sa-Sba reference line were statistically different from the real values (p<0.05). The values according to T-Ex reference line were statistically different for two parameters and not statistically different for remaining four parameters. Fort he frontal measurements, the values according to Ex-Ex, En-En and P-P lines were statistically different from the real values for all parameters. When the study group was assessed entirely, it was found that T-Ex and Ex-Ex lines were the most reliable reference lines for the lateral and the frontal measurements, respectively.